Is a three-dimensional-printed tooth filling possible? - Muhammet Kerim Ayar (Wolters Kluwer Medknow Publications, 2016)
Introduction: Three-dimensional (3-D) printing is seen as an innovative production process in many fields of dentistry and medicine. But implantation of this novel production process into the treatment of decayed teeth in dentistry remains lacking. Destruction of dental tissues as a result of dental caries is generally treated with dental resin composite fillings. However, a 3-D-printed tooth filling approach, which could be an alternative to traditional approaches, has a potential to reduce treatment costs and technique-sensitivity of the placement of restorative material. The Hypothesis: Here, the hypothesis that a 3-D-printed tooth filling approach could be an alternative to traditional approaches to treatment of decayed teeth is proposed. Evaluation of the Hypothesis: The actual implementation of the 3-D-printed tooth filling technique in the practice of restorative dentistry was discussed in this manuscript.